IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TEMA REKAYASA TEKNOLOGI DALAM PENGUATAN KETERAMPILAN 4C PADA SISWA SEKOLAH DASAR - Nurul Hidayah; Ngabiyanto; Wadiyo Wadiyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Technological Engineering in strengthening 4C skills (Communication, Collaboration, Critical Thinking, and Creativity) for elementary school students. The Merdeka curriculum implemented in Indonesia emphasizes the importance of strengthening student character through project-based learning. This research was conducted at SD Labschool UNNES with a descriptive qualitative approach, using observation, interview, and documentation techniques to collect data. The results showed that the implementation of P5 with the theme of Technological Engineering was able to strengthening students' critical thinking, communication, creativity, and collaboration skills through various projects, such as making creative houses, aesthetic lanterns, swing wheels, and simple robots. In addition, the integration of technology in learning also helps students understand technology concepts more deeply and applicatively. Therefore, the implementation of P5 based on Engineering Technology can be an effective strategy in strengthening 4C skills for elementary school students.